Quantification of bris soil variability and response of kenaf (Hibiscus cannabinus L.) to various depths and types of spodic horizon - Ahmed, Khalil (2012)
BRIS soils are inherently variable with various depths and types of spodic horizons. However, limited research has been conducted in characterizing and managing the BRIS soil for kenaf production in Malaysia. The objectives of the study were, to quantify the spatial variability of BRIS soil and to identify the yield limiting factors of kenaf for delineating the management zone strategy. The effect of different depths and types of spodic horizons was also determined on growth, yield and root morphology of kenaf. The study consists of two field experiments and one glass house experiment. For the first field study, geo-referenced soil samples at two depths (0-15 and 15-30 cm) and plant samples of kenaf were collected. Geostatistical techniques were applied to characterize the spatial variability of the studied area to delineate the management zones. In the second field study effect of different depths of spodic horizon was investigated on growth, root morphology and yield of kenaf. Four locations with different depths of spodic horizons L1=20, L2=48, L3=77 and L4=118 cm were selected and morphological characteristics of soil were determined. Locations one and two are classified as Rhu Tapai series whereas; locations 3 and 4 belong to Rudua and Jambu series. A glass house study was conducted to observe the response of kenaf (growth, root morphology and yield of kenaf) to different types of spodic horizons. For this purpose, four types of undisturbed spodic horizons with the strengths S1=3.88, S2=5.03, S3=5.82, S4=8.05 and a control 0.14 kg cm-2 (without spodic) were collected in PVC columns. Water filled pore space, air filled pore space and total pore space were determined in different types of spodic horizons. Roots of kenaf were sampled at 10, 20 and 30 cm depths from each type of spodic horizons with a metal box sized 0.01-0.01m2 for morphological studies. The results of geostatistical analysis showed moderate spatial dependence for TC, TN, P, Ca, Mg, CEC and yield of kenaf indicating that the extrinsic factor such as levelling of ridges and management practices for more than three decades restructured the variability of BRIS soil properties. At surface soil pH, TN and Mg were quantified into two management zones, while at sub-surface they were quantified into one management zone. TC and CEC were quantified into one management zone while P and Ca were quantified into two management zones at both the depths. The yield of kenaf was also quantified into two management zones. The negative correlation of TC, TN and Ca with sand content indicating the low fertility level of BRIS soil. It was also observed that the soil properties like bulk density, sand, silt, porosity, pH, P, K, Ca and Mg did not show the significant correlation with the yield of kenaf. Morphological features of four soils studied showed differences in the depth and thickness of horizons. The thickness of albic horizon at Rhu Tapai series was 10 and 38 cm while 67 and 102 cm were observed in Rudua and Jambu soil series. Texture of all the BRIS soil horizons was sandy in nature. Porosity percentage, P, K, Ca and Mg were observed higher in spodic horizons than top infertile horizons. Average soil surface temperature was in the order of Rhu Tapai < Rudua < Jambu series. The depth of spodic horizon had a significant effect on plant height, number of nodes, leaf area, diameter and dry matter yield of kenaf as the negative linear relationship. Stalk yield of kenaf declined by 13.60, 20.52 and 37 % at 48, 77 and 118 cm depth of spodic horizon in the soil profile. Visually, the growth in the roots of kenaf was stunted with the increase in depth of spodic horizon. Different types of spodic horizons had a significant effect on growth, yield and root morphology of kenaf. Spodic type four was significantly higher in water filled pore space and lower in air filled pore space as compared to S1, S2, S3 and control. At 60 days of kenaf growth plant height, leaf area, dry weight of stem and bark were significantly higher in S4 than S1, S2, S3 and control. The spodic types were significantly affected the root morphology of kenaf and the deformation of main root occurred at the strength of 8.05 kg cm-2 in spodic type S4. It is concluded that the mixing of spodic horizon with top infertile horizons create moderate spatial variability in the properties of BRIS soil, which affects the yield of kenaf where application of site specific management zone strategy is required. The depth and types of spodic horizons had significant effect on growth, root morphology and yield of kenaf and need to be considered in the planting of kenaf on BRIS soil.